Effect of Novel Antipsychotics on Energy Metabolism - In Vitro Study in Pig Brain Mitochondria - Ľupták, Matej; Fišar, Zdeněk; Hroudová, Jana (Molecular neurobiology, 2021)
The identification and quantification of mitochondrial effects of novel antipsychotics (brexpiprazole, cariprazine, loxapine, and lurasidone) were studied in vitro﻿ in pig brain mitochondria. Selected parameters of mitochondrial metabolism, electron transport chain (ETC) complexes, citrate synthase (CS), malate dehydrogenase (MDH), monoamine oxidase (MAO), mitochondrial respiration, and total ATP and reactive oxygen species (ROS) production were evaluated and associated with possible adverse effects of drugs. All tested antipsychotics decreased the ETC activities (except for complex IV, which increased in activity after brexpiprazole and loxapine addition). Both complex I- and complex II-linked respiration were dose-dependently inhibited, and significant correlations were found between complex I-linked respiration and both complex I activity (positive correlation) and complex IV activity (negative correlation). All drugs significantly decreased mitochondrial ATP production at higher concentrations. Hydrogen peroxide production was significantly increased at 10 µM brexpiprazole and lurasidone and at 100 µM cariprazine and loxapine. All antipsychotics acted as partial inhibitors of MAO-A, brexpiprazole and loxapine partially inhibited MAO-B. Based on our results, novel antipsychotics probably lacked oxygen uncoupling properties. The mitochondrial effects of novel antipsychotics might contribute on their adverse effects, which are mostly related to decreased ATP production and increased ROS production, while MAO-A inhibition might contribute to their antidepressant effect, and brexpiprazole- and loxapine-induced MAO-B inhibition might likely promote neuroplasticity and neuroprotection. The assessment of drug-induced mitochondrial dysfunctions is important in development of new drugs as well as in the understanding of molecular mechanism of adverse or side drug effects.
Keywords: energetický metabolismus; prasata; Swine; Mitochondria; adenosintrifosfát; elektronový transportní řetězec; Reactive oxygen species; Piperazines; thiofeny; Monoamine oxidase; reaktivní formy kyslíku; chinolony; Dopamine system stabilizers; Lurasidone Hydrochloride; Monoamine Oxidase Inhibitors; piperaziny; Receptors, Neurotransmitter; peroxid vodíku; lurasidon hydrochlorid; inhibitory MAO; Electron Transport Chain Complex Proteins; Hydrogen Peroxide; Oxidative phosphorylation; Quinolones; Loxapine; Reactive Oxygen Species; spotřeba kyslíku; receptory neurotransmiterů; Oxygen Consumption; Animals; loxapin; Energy Metabolism; zvířata; Mitochondrial respiration; Adenosine Triphosphate; Thiophenes; ATP; Antipsychotic Agents; mitochondrie; antipsychotika